Elemental imbalance and oxidative biomarker shifts in lumbar disc degeneration - Strojny, Damian; Wojdyła, Roman; Skóra, Klaudia; Hoczela, Martyna; Wyczarska-Dziki, Katarzyna; Rajchel, Mateusz; Miller, Mateusz; Sobański, Dawid; Staszkiewicz, Rafał; Wieczorek, Jerzy; Chwalba, Artur; Rogoziński, Przemysław; et al. (Frontiers in Neurology, 2025)
IntroductionThe pathogenesis of intervertebral disc degeneration (IVDD) involves multifactorial biochemical and metabolic disturbances; however, the contribution of trace elements and oxidative stress to this process remains insufficiently characterized. Understanding alterations in elemental composition and redox homeostasis within degenerated discs may reveal novel aspects of IVDD biology and potential therapeutic targets.MethodsThis study analyzed lumbar intervertebral disc (IVD) tissue obtained from 200 patients undergoing microdiscectomy for lumbosacral IVDD and 100 postmortem controls without disc degeneration. The concentrations of zinc (Zn), magnesium (Mg), calcium (Ca), phosphorus (P), iron (Fe), manganese (Mn), copper (Cu), lead (Pb), sodium (Na), and potassium (K) were quantified using inductively coupled plasma optical emission spectrometry (ICP-OES). Oxidative stress status was assessed by measuring thiobarbituric acid reactive substances (TBARs; nmol MDA/mg protein), reduced glutathione (GSH; μmol/g tissue), and glutathione peroxidase (GPx; U/mg protein). Elemental concentrations were analyzed in relation to Pfirrmann degeneration grade, body mass index (BMI), and pain severity.ResultsDegenerated discs exhibited significantly higher concentrations of Zn (35.10 ± 22.00 vs. 22.30 ± 14.00 mg/kg, p = 0.027), Mg (62,000 ± 80,000 vs. 130 ± 90 mg/kg, p < 0.0001), Ca (6,100 ± 13,900 vs. 1,500 ± 730 mg/kg, p < 0.0001), and P (5,000 ± 5,500 vs. 1,600 ± 1,340 mg/kg, p < 0.0001) compared with controls. Zn concentrations peaked in Pfirrmann grade 4 discs, while Mg was highest in grades 2 and 5 (p < 0.001). Ca and P levels were independent of degeneration grade but significantly elevated in obese patients (p < 0.001). In contrast, Mg concentrations were greatest in patients with normal BMI and declined with increasing BMI (p < 0.001). No significant correlations were observed between element concentrations and pain intensity (p > 0.05). Oxidative stress parameters indicated elevated TBARs (5.52 ± 2.52 vs. 2.63 ± 0.97, p < 0.0001), increased GPx activity (69.45 ± 3.92 vs. 60.25 ± 3.52, p = 0.027), and a non-significant reduction in GSH (p = 0.054). Strong positive correlations were found between P and Ca (r = 0.93, p < 0.001) and between K and Mn (r = 0.80, p < 0.001).DiscussionThese findings reveal substantial alterations in the micro- and macronutrient composition of degenerated IVDs, particularly for Zn, Mg, Ca, and P, suggesting that metabolic dysregulation and mineral imbalance contribute to disc pathology. The observed oxidative stress profile, characterized by lipid peroxidation and compensatory GPx activation, supports the involvement of redox imbalance in IVDD progression. Together, these results underscore the interplay between mineral homeostasis, oxidative stress, and disc degeneration, providing potential avenues for biomarker development and metabolic intervention in IVDD management.